2021
DOI: 10.1186/s13048-021-00884-z
|View full text |Cite
|
Sign up to set email alerts
|

TTK is a potential therapeutic target for cisplatin-resistant ovarian cancer

Abstract: Background Drug resistance and recurrence are main contributors to the poor prognosis of ovarian cancer. Cisplatin is a platinum compound which is widely used in the treatment of various solid tumors including ovarian cancer. Up to now, the mechanism of cisplatin resistance in ovarian cancer is unclear. Threonine and tyrosine kinase (TTK), an integral part of the spindle assembly checkpoint, may be a potential new target associated with chemotherapy sensitivity. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…However, >10% apoptosis and dead A2780cis cells were observed even at 0 h (non-treated cell group). This effect could be due to cell death during experimental protocol, which has been previously reported ( 45 , 46 ). Therefore, additional assays on the apoptosis of non-treated (0 h) cells at 24, 48 and 72 h were performed to verify the effects of trans-(±)-kusunokinin on apoptosis at 72 h ( Fig.…”
Section: Discussionmentioning
confidence: 51%
“…However, >10% apoptosis and dead A2780cis cells were observed even at 0 h (non-treated cell group). This effect could be due to cell death during experimental protocol, which has been previously reported ( 45 , 46 ). Therefore, additional assays on the apoptosis of non-treated (0 h) cells at 24, 48 and 72 h were performed to verify the effects of trans-(±)-kusunokinin on apoptosis at 72 h ( Fig.…”
Section: Discussionmentioning
confidence: 51%
“…TTK is overexpressed in cisplatin-resistant ovarian cancer cells and ovarian cancer patients with acquired resistance to cisplatin. TTK knockdown increases the sensitivity of cisplatin-resistant ovarian cancer cells to cisplatin via the PI3K/AKT signaling pathway [ 27 ]. Inhibition of TTK alters cell-cycle progression and exacerbates centrosome abnormalities, thus promoting the radiosensitivity of liver cancer cells in a p21-mediated manner [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the colorectal and glioblastoma in vitro models, the inhibition of TTK expression pharmacologically decreases cell viability, resulting in abnormal cell cycle progression, elevated aneuploidy, and induced apoptosis ( Yao et al, 2021 ). TTK activity is crucial for pancreatic cancer cell proliferation, making TTK a potential therapeutic target for new treatments ( Liu et al, 2021 ). Additionally, TTK was evaluated as a potential prognostic biomarker for triple-negative BC and it was demonstrated that increased TTK expression is associated with improved disease-free survival and OS, with a better prognosis ( Xu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%